(untitled) (Comparative & International Education Series, 2021)
In this introductory chapter of the book, we discuss what the commercialization of study abroad meant for the equity in study abroad and student mobility. Is the business model of international higher education gradually pulling away from the goal it was meant to serve? How can scholars, policymakers and educational practitioners ensure that study abroad is not reinforcing the social inequality present in societies and the world?